EdTech to Support Out-of-School Children and Adolescents - Thinley, Sangay; Rui, Yang (EdTech Hub, 2023)
This Helpdesk report was created in response to a request from the World Bank Malawi Education Team for a curated list of resources on examples of EdTech interventions targeting out-of-school children and adolescents to inform an ASA (Advisory Services and Analytics) output. The ASA output will provide policy options to improve second-chance learning and foundational skills for out-of-school children (OOSC). To provide the World Bank Malawi team with adequate information on the above. This curated list begins with an introduction to the use of EdTech to support out-of-school children and youth, and then moves on to present examples of such interventions and programmes within Malawi, as well the wider African region and the rest of the world. This list is designed to serve as a resource for the team and does not make any direct recommendations on actions to be taken. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7906889 ZenodoArchiveConcept: 7906888 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7906875 10.5281/zenodo.7906889 10.53832/edtechhub.0163 2339240:2LWVXYCV 2405685:4CB23ZC6 2405685:AG764A26 2405685:VWJXTPI8
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Summary: EdTech for Out-of-School Children and Youth - A Rapid Evidence Review for the Southeast Asian Region - Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D’Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
This document is a summary of a rapid evidence review on EdTech for Out-of-School Children and Youth produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/.An output of the EdTech Hub, https://edtechhub.org/ An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12819080 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1044 ZenodoArchiveConcept: 12819079
Keywords: _r:AddedByMyEducationEvidence

EdTech for Learners With Hearing and Visual Impairments: A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D'Rozario, Jonny (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with hearing and visual impairments. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education forlearners with hearing and visual impairments, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; visual impairments; hearing impairments; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11197419 ZenodoArchiveConcept: 11197418 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1027 10.53832/edtechhub.1028 2405685:DQ9GNC3J 2405685:M6A4ZHJ3
Keywords: _r:AddedByMyEducationEvidence

Summary: Out-of-School Children and Youth - A Rapid Evidence Review for the Southeast Asian Region - Afzal, Nimra; Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D’Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 12819080 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1044 ZenodoArchiveConcept: 12819079
Keywords: _comingsoon; _r:AddedByMyEducationEvidence